ChemInform Abstract: Cassaine Diterpene Alkaloids from Erythrophleum fordii and Their anti‐Angiogenic Effect. Issue 18 (17th April 2014) - Hung, Tran Manh; Cuong, To Dao; Kim, Jeong Ah; Tae, Nara; Lee, Jeong Hyung; Min, Byung Sun
Abstract: Two new compounds, erythroformide (I) and 3β‐acetoxynorcassamide (II), are isolated together with four known compounds and their effects on endothelial tube formation on matrigel are investigated.